Konsep Pendidikan Multikultural Dalam Perspektif Pendidikan Islam - Ilham Mirsal (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2017)
This paper discusses about multicultural education that is a concept of educationembracing an approach and a transformation to provide students and all the people anunderstanding to appreciate and respect the diversity owned by a nation. The conceptto appreciate and respect diversity has been taught in Islam through the Qur’an so thatpeople can see differences and appreciate the diversity they have, such as tribes, religions,cultures, and others. Multicultural education as a concept of education that forms a socialparadigm encourages schools to take part in instilling awareness of the multiculturalcommunity and growing attitude of tolerance to actualize the need and the ability to worktogether among the diversity existed. In this regard, this paper shall show that the practiceof multicultural education in Indonesia is potential to be conducted flexibly rather thanas a separated lesson or in a monolithic manner. The implementation of multiculturaleducation is based on 5 dimensions. (1) Content integration, (2) knowledge constructionprocess, (3) reducing prejudice, (4) equal pedagogy, and (5) empowered school cultureand structure